Intra Party Conflict and Electoral Performance: The Experience of the Peoples Democratic Party in the 2023 Nigeria’s Presidential Election - Adamu, Abdulrahman; Yusufu, Ahmed Audu (Kashere Journal of Politics and International Relations, 2025)
This paper investigated the issues that gave rise to the internal conflict in the PDP at the national level prior to the 2023 presidential election, and argues that it adversely affected its performance at the poll. To support this argument, the paper deployed intra-group conflict theory as a framework of analysis, and generated data from primary sources such as Structured Questionnaire (SQ) and Key Informant Interview (KII), and secondary sources such as books, journals, newspapers/magazines and online materials among others. Data generated from the field survey using SQ were presented in tables and descriptively analysed while the contents of data collected via KII were qualitatively analysed. Research hypotheses were tested at 5% level of significance using non parametric statistics (chi square). The paper found weak internal democracy, desperation for power, clash of irreconcilable interests, and poor conflict resolution mechanism among others as responsible for the internal crisis in the PDP. The paper equally found that intra-party conflict in the PDP manifested in the forms of personality clash between Governor Nyesom Wike and Senator Iyorchia Ayu and media war with the resultant consequences of incessant defections and dwindling party membership among others. Based on these findings, the paper concluded that PDP may still suffer more political woes in future presidential elections if urgent steps are not taken to address the conflict. Based on the findings and conclusion drawn, the paper recommended, among others that, the contentious issues responsible for the internal strife in the party should be amicably resolved as soon as possible for the party to be able to reclaim power from the ruling All Progressives Congress (APC).